Hubungan Self-Care dengan Kualitas Hidup Penderita Diabetes Melitus di Wilayah Kerja UPTD Puskesmas Rawat Inap Sragi Tahun 2024 - meisita, ita; Andini, Sandra; Warni, Hernida (Universitas Aufa Royhan, 2025)
The objective of this study is to establish the relationship between self-care and quality of life among patients diagnosed with diabetes mellitus in the working area of the Sragi Community Health Centre in 2024. The researcher employed a quantitative observational analytical method and applied a cross-sectional approach. The study cohort consisted of 113 individuals diagnosed with diabetes mellitus, under observation from January to April. Purposive sampling, which involved careful consideration of specific criteria for inclusion and exclusion, selected a total of 88 participants among these. For our investigation, we used the SDSCA and DQoL questionnaires. We performed data analysis using frequency distributions and chi-square testing. The results revealed that a substantial percentage of the participants (43.2%) reported experiencing a moderate degree of self-care and quality of life. The p-value of 0.000 indicates a significant and robust connection between self-care and quality of life. Researchers encourage that persons diagnosed with diabetes mellitus improve their self-care habits in order to reduce complications and improve their overall quality of life